Surface‐sampling mass spectrometry and imaging: Direct analysis of bacterial species. (17th November 2020) - Griffiths, Rian L.
Abstract : Surface‐sampling mass spectrometry and imaging techniques offer the opportunity to directly interrogate a wide range of surfaces. Ambient techniques have become popular as samples can be analysed at room conditions with little to no sample preparation. However, more traditional (vacuum based) techniques offer superior spatial resolution imaging. This review aims to offer an overview of the capabilities of some of the most widely used surface mass spectrometry and imaging techniques with a particular focus on the analysis of bacterial samples. The relative benefits of each approach and the differences in capabilities will be discussed. The complementarity of different approaches will also be described in the context of bacterial analysis. Different applications in terms of sample types and biomolecules analysed (within the context of bacterial samples) will be discussed and perspectives offered on which developments may play key roles in the future.